Space traffic management terminology. Issue 4 (December 2022) - Skinner, Mark A.; Oltrogge, Dan; Strah, Maruska; Rovetto, Robert J.; Lacroix, Andre; Kumar, A K Anil; Grattan, Kyran; Francillout, Laurent; Alonso, Ines
Summary: The International Astronautical Federation (IAF) has several dedicated technical committees, including Technical Committee #26 (TC26), which deals with space traffic management (STM). TC26 was founded in October 2018 following a joint decision between the International Academy of Astronautics, the International Institute of Space Law, and the IAF at the International Astronautical Congress (IAC) in Bremen, Germany. TC26 is producing a white paper, with the final draft expected by the 2022 IAC in Paris, France. To accomplish this goal, TC26 formed 14 working groups chartered to examine terminology, new means of space object monitoring, improving orbital data, reentry hazards, improving the collision avoidance process, future space operations, new technical regulations, and compliance with existing technical regulations, among other topics. This paper presents the terminology working group's contributions to TC26's white paper. Aspects of this paper may differ from the final white paper, which will be harmonized with the reports developed by the other TC26 working groups. STM terminology is not universally harmonized today. In the following sections, we summarize the significance of effective STM, present the causes of the variance in terminology, and highlight the challenges to reaching consensus. We conclude by defining STM-related terms that will inform the final white paper of TC26.